2023
DOI: 10.3389/fgene.2023.1009462
|View full text |Cite
|
Sign up to set email alerts
|

Weighted gene co-expression network analysis identifies key hub genes and pathways in acute myeloid leukemia

Abstract: Introduction: Acute myeloid leukemia (AML) is the most common type of leukemia in adults. However, there is a gap in understanding the molecular basis of the disease, partly because key genes associated with AML have not been extensively explored. In the current study, we aimed to identify genes that have strong association with AML based on a cross-species integrative approach.Methods: We used Weighted Gene Co-Expression Network Analysis (WGCNA) to identify co-expressed gene modules significantly correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Network analysis of various molecular and regulatory factors [ 49 , 50 ] is a strong and widely used approach for exploring the underlying mechanisms of any disease. It has not only been used in AML research [ 51 53 ] but also for several other diseases and physiological conditions [ 54 56 ]. In the current study, we constructed protein-protein interaction network and revealed the close relationships among the m5C regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Network analysis of various molecular and regulatory factors [ 49 , 50 ] is a strong and widely used approach for exploring the underlying mechanisms of any disease. It has not only been used in AML research [ 51 53 ] but also for several other diseases and physiological conditions [ 54 56 ]. In the current study, we constructed protein-protein interaction network and revealed the close relationships among the m5C regulators.…”
Section: Discussionmentioning
confidence: 99%
“…found that the hub gene CEACAM5 is significantly associated with the prognosis of AML and can serve as a potential target for AML treatment. Wang et al 20 . identified a group of hub genes ( NFE2 , TRIM27 , MEF2C , ETS1 , TAL1 , FOXO1 and GATA1 ) and pathways in AML using WGCNA.…”
Section: Discussionmentioning
confidence: 99%
“…The weighted gene co‐expression network analysis (WGCNA) is a compelling method that utilizes big data to detect synergistically expressed genes related to clinical phenotypes rather than focusing on a single gene 17 . WGCNA has recently become widely used in various diseases, including AML, to identify target hub genes 18–21 . However, there is almost no overlap among these genes, and their mechanisms of action are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation